Accountability in Planning, Implementation and Accountability of Village Funds Based on Government Regulations - Junita Nana Ariantje; Lanemey Brigitha Pandeirot; Ika Prayanthi (International Journal on Social Science, Economics and Art, 2022)
This study aims to find out whether the principles of accountability related to accountability for the management of Village Funds which are carried out starting from the planning, implementation, accountability and supervision stages are properly implemented in Lembean Village, Kauditan District, North Minahasa Regency in 2015-2018. The method used in this research is a qualitative descriptive method with the object of research, namely Lembean Village. The data in this study are primary data obtained through interviews with related parties such as the Village Head, Village Secretary, Village Consultative Body and the community. The results of this study indicate that starting from the stages of planning, implementation, accountability and supervision are good and in accordance with applicable regulations and management has been carried out in an accountable and transparent manner.